Midwives' Knowledge of the Use of Personal Protective Equipment During the Covid-19 Pandemic at Mr. Rondahaim Pamatang Raya Regional Hospital Simalungun Regency - Utami, Ria Lusi; Friani, Sri Rahma; Manurung, Christina (PT Inovasi Pratama Internasional, 2022)
Pneumonia Coronavirus Disease 2019 or COVID-19 is a lung inflammation disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Personal Protective Equipment is a set of equipment that functions to protect its users from certain dangers or health problems, such as viral or bacterial infections. This research was conducted at Tn. Rondahaim Pamatangraya Regional Hospital, Simalungun Regency. This type of research is descriptive research conducted to describe or illustrate a phenomenon that occurs in society (Notoatmodjo, 2010). The purpose of this study was to determine the knowledge of midwives about the use of personal protective equipment during the Covid-19 pandemic at Tuan Rondahaim Pamatang Raya Regional Hospital, Simalungun Regency in 2020. The results of the study found that the majority of midwives at Tn. Rondahaim Regional Hospital already have a good level of knowledge. Of the 38 midwives working at Tuan Rondahaim Regional Hospital, it was found that 65.8% of respondents had good knowledge about the use of personal protective equipment. It is recommended for midwives to always comply with the use of personal protective equipment in accordance with standard operating procedures while working to prevent and reduce the risk of infection in hospitals.